Research of radiation impurity defects in the crystals of potassium sulphate activated by ions of the transitional metals - Koketai, Т.А.; Lushchik, А.Ch.; Tussupbekova, А.K.; Baltabekov, А.S.; Mussenova, E.K.; Ganyukova, А.А.; Ibragimov, А. (Вестник Карагандинского университета, 2016)
The radiation impurity defects in the crystals of potassium sulphate activated by ions of the transitional met- als was research in this work. According to spectra of optical absorption of K2SO4–Cо2+, K2SO4–Mn2+, K2SO4–Ni2+ crystals of research it is possible to draw qualitative conclusions on impurity and dot defects of objects. It is clear that after radiation by X-ray quantum the optical density in the impurity absorption bands of the crystals are decreases. This phenomenon is explained that there is a change of charging state at initial ions of divalent metal ions and the impurity ions either are ionized or are traps for electrons. It was found that the impuritу ions of the transition metals Ме2+ are the centers of electron capture in potassium sul- phate.
Keywords: ionic crystals; potassium sulphate; absorption spectrum; impurity ions; defect